Sadyry : ritual de iniciação masculina dos Kurâ-Bakairi - Pereira, Luís Alberto (2017)
This dissertation deals with the sadyry, ritual of masculine puberty among the Kurâ-Bakairi, Karib-speaking people who inhabit the cerrado of Mato Grosso, Brazil. The research in which it was conducted was held in Bakairi Indigenous Land, where there are ten local groups. The text is structured in three chapters. The first is dedicated to its history and social organization, as well as to the concepts of territory and territoriality. The second seeks to understand it from the experts of Sadyry, based on the mythical hero Tyna and his relationship with the ritual partners, iduno and iemamidâry. In the third one is the ethnography of Sadyry proper, centered on the day of the event and the subsequent ritual seclusion – wanke –, which is an integral part of the process of construction of the Kurâ person.